2003
DOI: 10.1590/s1516-84842003000300005
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos imunológicos da esquistossomose mansoni hepatoesplênica após cirurgia terapêutica

Abstract: A forma hepatoesplênica da esquistossomose mansoni pode apresentar complicações, como o sangramento de varizes esofágicas e gástricas, que requerem tratamento cirúrgico. Apesar de a esplenectomia ser freqüentemente necessária, esses pacientes raramente desenvolvem os fenômenos sépticos, que são mais freqüentemente encontrados em pessoas asplênicas do que na população em geral. Essa particularidade dos esquistossomóticos pode ser relacionada a alguma característica particular do sistema imune nessa afecção. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
0
3
1
1
Order By: Relevance
“…Finally, although some studies have reported no increase in sepsis resulting from schistosomiasis in association with splenectomy (12) (14) , we observed a higher prevalence of bacterial translocation to the peripheral blood in the schistosomotic and splenectomized mice compared with those that were only splenectomized or only schistosomotic. This fi nding may be associated with a weakened immune response due to the absence of the spleen and deterioration of the nutritional status fostered by both factors (Schistosoma infection and splenectomy).…”
Section: Discussioncontrasting
confidence: 87%
See 3 more Smart Citations
“…Finally, although some studies have reported no increase in sepsis resulting from schistosomiasis in association with splenectomy (12) (14) , we observed a higher prevalence of bacterial translocation to the peripheral blood in the schistosomotic and splenectomized mice compared with those that were only splenectomized or only schistosomotic. This fi nding may be associated with a weakened immune response due to the absence of the spleen and deterioration of the nutritional status fostered by both factors (Schistosoma infection and splenectomy).…”
Section: Discussioncontrasting
confidence: 87%
“…However, several studies have reported that the IgM level remains high, even after partial or total splenectomy (9) (10) (11) . This fi nding might help to explain the reduction in the infection rate that has been reported in splenectomized schistosomotic patients (12) (13) .…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…É importante mencionar que não há relato de sepse ou outra complicação comum depois de esplenectomia total após tratamentos conservadores, clínico ou cirúrgico do baço. 4,5 Uma outra afecção que merece destaque é o hiperesplenismo. Atualmente, os hematologistas dispõem de um considerável arsenal medicamentoso, cada vez mais eficaz, para controlar essa doença ainda não completamente compreendida e que apresenta diversos aspectos em comum com as leucoses.…”
Section: Andy Petroianuunclassified